BASIC APPROACHES TO QUALITY MANAGEMENT IN LOCAL GOVERNMENT - Mariekhin S.V. (Pressing Problems of Public Administration, 2016)
Main approaches to quality management in local authorities are considered. Two groups of these approaches are de ned. The application of different approaches, their advantages and  aws have been thoroughly scrutinized.